2022
DOI: 10.3390/gels8100682
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Crosslinking Degree of Hydrogels on Hydrogel Adhesion

Abstract: The development of adhesive hydrogel materials has brought numerous advances to biomedical engineering. Hydrogel adhesion has drawn much attention in research and applications. In this paper, the study of hydrogel adhesion is no longer limited to the surface of hydrogels. Here, the effect of the internal crosslinking degree of hydrogels prepared by different methods on hydrogel adhesion was explored to find the generality. The results show that with the increase in crosslinking degree, the hydrogel adhesion de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Figure A displays the different adhesive stress vs strain profiles, revealing an increase in the materials’ tackiness with the amount of TA@CNC added. Figure B, red and blue columns, represents this increasing tendency of tackiness and energy of adhesion . This trend is reasonably expected because the TA that coats the CNCs promotes H-bonding formation and thus enhances the adhesion energy values …”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Figure A displays the different adhesive stress vs strain profiles, revealing an increase in the materials’ tackiness with the amount of TA@CNC added. Figure B, red and blue columns, represents this increasing tendency of tackiness and energy of adhesion . This trend is reasonably expected because the TA that coats the CNCs promotes H-bonding formation and thus enhances the adhesion energy values …”
Section: Resultssupporting
confidence: 60%
“…Figure 4B, red and blue columns, represents this increasing tendency of tackiness and energy of adhesion. 52 This trend is reasonably expected because the TA that coats the CNCs promotes H-bonding formation and thus enhances the adhesion energy values. 33 Although the tackiness values of BioeGels are lower than those of recently reported gelatin eutectogels 18 but higher than that of CNC nanocomposite hydrogels, 33,52 the magnitude of the adhesion force of our ionic materials is good enough to be able to adhere to human skin.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The degree of swelling, a gravimetric measure used to study the cross-linking density of a hydrogel, was an essential parameter to evaluate the adhesive and cohesive properties, as well as the drug release. Cross-linking strategies were used to control the rate and the extent of the hydration required to achieve sustained adhesion [ 54 ]. As reported in the literature, high swelling values were related to lower cross-linking densities [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different crosslinking methods and crosslinking degrees affect the properties of obtained hydrogels. To study the effect of the crosslinking degree on the adhesivity of hydrogels, Li et al prepared polyvinyl alcohol (PVA), polyacrylamide (PAM) and polyvinyl alcohol-bearing styrylpyridinium group (PVA-SbQ) hydrogels through freeze–thaw cycles, thermal crosslinking and photo-crosslinking, respectively [ 4 ]. They found that the adhesion capability of these hydrogels decreased with an increase in the crosslinking degree.…”
mentioning
confidence: 99%